2014
DOI: 10.3413/nukmed-0680-14-06
|View full text |Cite
|
Sign up to set email alerts
|

Real-time ultrasound and freehand-SPECT

Abstract: The fusion imaging concept combining SLN information with ultrasound images presented here proves to be feasible and technically successful. However, significant technical limitations were shown in fh-SPECT quality and fusion precision. Subject to technical optimisation of SPECT quality and co-registration, a meaningful contribution to the preoperative planning of lymph node therapy is imaginable. Thus, fundamentally a preoperative histological examination by fh-SPECT/US-guided biopsy is possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…Two recently developed techniques for improved SN identification peri-operatively are SPECT-US [38, 39], and near infrared light fluorescence imaging [40–44]. SPECT-US displays the location of a radio-active SN in the US images; making it easier for the surgeon to locate SN’s in anatomically challenging area’s such as the cervical and occipital area; or to guide radiologists for FNAC [38, 39].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two recently developed techniques for improved SN identification peri-operatively are SPECT-US [38, 39], and near infrared light fluorescence imaging [40–44]. SPECT-US displays the location of a radio-active SN in the US images; making it easier for the surgeon to locate SN’s in anatomically challenging area’s such as the cervical and occipital area; or to guide radiologists for FNAC [38, 39].…”
Section: Introductionmentioning
confidence: 99%
“…SPECT-US displays the location of a radio-active SN in the US images; making it easier for the surgeon to locate SN’s in anatomically challenging area’s such as the cervical and occipital area; or to guide radiologists for FNAC [38, 39]. Near infrared light fluorescence imaging is conducted with Indocyanine green as tracer, which can be combined with 99Tc nano-colloids to form a hybrid tracer [41].…”
Section: Introductionmentioning
confidence: 99%
“…10 Recently, the fusion of these 3D nuclear images with US, making SN visualization on US possible, was introduced. 11,12 In this setup, functional (fully 3D freehand SPECT) and anatomic (2D ultrasound) information are combined in real-time.…”
mentioning
confidence: 99%
“…Freesmeyer et al 11,12 showed that freehand SPECT-US was feasible and technically successful in patients with breast cancer, melanoma, and thyroid disease. However, some technical limitations were shown in freehand SPECT quality and fusion precision.…”
mentioning
confidence: 99%
“…The most established RGS form of this, and the only one being applied in vivo yet, is freehand SPECT [97]. Combining this technology with a tracked US device, intraoperative freehand SPECT/US has also made it to patients [114][115][116][117]. Preclinical research has also been performed to investigate freehand imaging of beta emissions [95,118], high-energy gamma emissions [119], or even freehand PET imaging using a coincidence or time-offlight principle with multiple detectors [120,121].…”
Section: Y)mentioning
confidence: 99%